2010
DOI: 10.1159/000316311
|View full text |Cite
|
Sign up to set email alerts
|

Voice Activity and Participation Profile in Assessing the Effects of Voice Disorders on Quality of Life: Estimation of the Validity, Reliability and Responsiveness of the Finnish Version

Abstract: Aim: The purpose of this study was to evaluate the validity, reliability and responsiveness of the Finnish version of the Voice Activity and Participation Profile (VAPP), a self-assessment questionnaire to measure psychosocial limitations caused by voice disorders. Methods: The study was conducted in Tampere University Hospital in 2004 and 2005. Voice patients (n = 142) with diverse chronic voice pathologies received 3–5 sessions of voice therapy. Controls were known individuals with healthy voices (n = 127). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…According to our previous work, VAPP is a robust instrument with a Cronbach's alpha coefficient of 0.958 and the test-retest reliability of 0.905. 24,25 In our previous work, it was found that the medical consultation did not have essential effect on VAPP (effect size À0.03), but significant improvement was found immediately after brief voice therapy (effect size 0.43). The results showed that 70% of the patients experienced a slight to moderate effect and 20% a strong effect (effect size more than 0.87).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…According to our previous work, VAPP is a robust instrument with a Cronbach's alpha coefficient of 0.958 and the test-retest reliability of 0.905. 24,25 In our previous work, it was found that the medical consultation did not have essential effect on VAPP (effect size À0.03), but significant improvement was found immediately after brief voice therapy (effect size 0.43). The results showed that 70% of the patients experienced a slight to moderate effect and 20% a strong effect (effect size more than 0.87).…”
Section: Introductionmentioning
confidence: 94%
“…28 SEM for VAPP total score was 15.1 mm (N ¼ 76). 25 For effect size calculations, Cohen's d was used. Effect size equal to 0.2 was taken to mean a slight effect, equal to 0.5 a moderate effect, and 0.8 a strong effect.…”
Section: Statisticsmentioning
confidence: 99%
See 3 more Smart Citations